COMMENTS ON THE ARTICLE BY I.YU. SMIRNOVA «ROLE OF NEURONAL NO-SYNTHASE GENE POLYMORPHISM IN FORMATION OF ATOPIC DERMATITIS IN CHILDREN AND IN SENSITIVITY TO THERAPY» - A.Yu. Asanov (Union of pediatricians of Russia, 2009)
.